IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK PADA MASA PANDEMI COVID-19 DI KOTA TANGERANG SELATAN (Studi Pada Klaster Hak Sipil dan Kebebasan) - Anggun Prasetya; Abdul Rahman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2022)
Child protection in Indonesia is a policy imperative, there are 80 million childrenscattered in various regions where their rights must be fulfilled. The Indonesiangovernment seeks to fulfill child protection by initiating the KLA program (Cityfor Children) in 2005 to accelerate the Convention on the Rights of the Child. Thepurpose of this study was to analyze the implementation of the KLA policy in South Tangerang City during the pandemic by using the Van Meter and Van Hornpolicy implementation model indicators. This research method uses a descriptivemethod with a qualitative approach. Data collection techniques throughobservation, interviews and documentation. The results showed that of the 6dimensions measured (Policy Size and Objectives, Resources, Characteristics ofImplementing Agencies, Attitudes or Tendencies, Inter-OrganizationalCommunication, Economic, Social, Political Environment) in general theimplementation of the City Eligibility policy during the pandemic in SouthTangerang City. good enough. However, the dimensions of resources and thedimensions of communication between organizations are still the biggestchallenges. Budget constraints are the cause of the non-optimal dimensions ofresources. On the other hand, policy socialization activities to the public are stillnot massive, and understanding of policy substance among policy implementersstill needs to be improved. Therefore, this study recommends that policysocialization to the public can be intensified. In addition, increasingunderstanding of the substance of the policy to the implementers also needs to beencouraged